Teaching Biology in the Field: Importance, Challenges, and Solutions. (5th May 2017) - Fleischner, Thomas L.; Espinoza, Robert E.; Gerrish, Gretchen A.; Greene, Harry W.; Kimmerer, Robin Wall; Lacey, Eileen A.; Pace, Steven; Parrish, Julia K.; Swain, Hilary M.; Trombulak, Stephen C.; Weisberg, Saul; Winkler, David W.; et al.
Abstract: Learning that occurs in a field setting is a powerful experience that promotes the development of new generations of creative scientists, enhances environmental literacy, and instills social responsibility in our citizens. Institutional challenges to field studies include decreasing financial resources and increasing regulatory concerns. These are coupled with changing student interests, in particular the growing misconception that field study is not relevant to many biological careers. Collectively, these factors contribute to a significant decline in field-study opportunities for students and lack of pedagogical guidance for instructors interested in conducting field courses. Nature and culture are inextricably linked, and we all benefit from including diverse backgrounds and perspectives in field experiences. We suggest expanding the definition of "the field" to include human-influenced ecosystems, as well as more conventional natural habitats. More than ever, the world needs the passion, insight, and wisdom that come from field studies.